Investigating the mode of action of sulfoxaflor: a fourth‐generation neonicotinoid. Issue 5 (30th October 2012) - Cutler, Penny; Slater, Russell; Edmunds, Andrew JF; Maienfisch, Peter; Hall, Roger G; Earley, Fergus GP; Pitterna, Thomas; Pal, Sitaram; Paul, Verity‐Laura; Goodchild, Jim; Blacker, Melissa; Hagmann, Leonhard; et al.
Abstract Background The precise mode of action of sulfoxaflor, a new nicotinic acetylcholine receptor‐modulating insecticide, is unclear. A detailed understanding of the mode of action, especially in relation to the neonicotinoids, is essential for recommending effective pest management practices. Results Radiolabel binding experiments using a tritiated analogue of sulfoxaflor ([3H]‐methyl‐SFX) performed on membranes from Myzus persicae demonstrate that sulfoxaflor interacts specifically with the high‐affinity imidacloprid binding site present in a subpopulation of the total nAChR pool. In competition studies, imidacloprid‐like neonicotinoids displace [3H]‐methyl‐SFX at pM concentrations. The effects of sulfoxaflor on the exposed aphid nervous system in situ are analogous to those of imidacloprid and nitenpyram, and finally the high‐affinity sulfoxaflor binding site is absent in a Myzus persicae strain (clone FRC) possessing a single amino acid point mutation (R81T) in the β‐nAChR, a region critical for neonicotinoid interaction. Conclusion The nicotinic acetylcholine receptor pharmacological profile of sulfoxaflor in aphids is consistent with that of imidacloprid. Additionally, the insecticidal activity of sulfoxaflor and the current commercialised neonicotinoids is affected by the point mutation in FRC Myzus persicae. Therefore, it is suggested that sulfoxalfor be considered a neonicotinoid, and that this be taken into account when recommending insecticide rotation partnering for effective resistance management programmes. © 2012 Society of Chemical Industry